Public administration facing pandemic challenges - a contribution to the discussion - Janik, Marcin (Scientific Journal of Bielsko-Biala School of Finance and Law, 2022)
This publication focuses on the identification and discussion of selected issues related to combating the SARS-CoV-2 epidemic whose extraordinary nature showed that the administrative paradigm used up to that point in time proved insufficient in standard environment. The emergency measures applied changed the way public authorities acted by interfering with individual rights and freedoms, going far beyond the so-called ordinary constitutional measures permitted by the Constitution outside the state of emergency. The legal regime in force corresponded to a large extent to the constitutional characteristics of a state of emergency. The discussion also covered the issue of hybrid or non-normative states of emergency, which is interesting in many respects.